1997
DOI: 10.1176/ajp.154.10.1454
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone pulse characteristics in depressed women

Abstract: M ajor depression is a common disorder that will affect at least 10% of women (DSM-III-R, p. 229). It is associated with abnormal hypothalamic regulation of a variety of neuroendocrine systems. If this dysregulation affects the hypothalamic-pituitary-gonadal (HPG) axis, potential physiologic manifestations could include impaired fertility, a condition of increasing clinical and social relevance for which an estimated 3 million couples sought treatment in 1995 (1).Regulation of the HPG axis depends on hypothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A study in 1997 reported that depressed women had higher LH amplitudes. However, there was no significant difference in the number of LH pulses over an eight-hour period [25]. In the year 2000, Young et al conducted a similar study on reproductive-age women with major depressive disorder.…”
Section: Figure 1: Depression Affecting Reproductive Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in 1997 reported that depressed women had higher LH amplitudes. However, there was no significant difference in the number of LH pulses over an eight-hour period [25]. In the year 2000, Young et al conducted a similar study on reproductive-age women with major depressive disorder.…”
Section: Figure 1: Depression Affecting Reproductive Hormonesmentioning
confidence: 99%
“…It is pertinent that these menopausal changes in women's life are associated with mood symptoms [16,41]. As discussed ahead, it is established that depression affects the reproductive hormone regulation in females [25,26,29]. Thus, it is significant to explore the association between depression and menopause.…”
Section: Depression and Its Association With Earlier Menopausementioning
confidence: 99%
“…In another study, IVF women had lower depressive symptoms than spontaneous pregnancy women at the third trimester of pregnancy, but the difference disappeared three months postdelivery; furthermore, the former had higher anxiety scores than the latter at the third trimester and the difference was maintained three months postdelivery [40]. Proposed underlying mechanisms include hyperprolactinemia, alterations in the regulation of the hypothalamic-pituitary-adrenal (HPA) and gonadotropin-luteinizing hormone (GnRH-LH) axes, and hyper-or hypothyroidism [41,42]. Other stress-related factors, such as low socioeconomic status, living in the inner city or degraded neighborhoods, and alcohol habits, may trigger anxiety and depressive symptoms and in turn negatively affect libido, thus resulting in infertility [43].…”
Section: Introductionmentioning
confidence: 99%